PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE MAKE A MATCH UNTUK MENINGKATKAN HASIL BELAJAR SISWA PADA TEMA PRAJA MUDA KARANA DI KELAS III SD PAB 23 PATUMBAK - Wiky Syahfitri; Tiflatul Husna (Jurnal Cakrawala Ilmiah, 2025)
This study aims to determine the effectiveness of the Make a Match cooperative learning model to improve student learning outcomes in thematic learning theme 8 "Praja Muda Karana". This research is a class action research (Classroom Action Research). The subjects in this study were 27 graders of SD PAB 23 Patumbak, 11 male students and 16 female students. Instruments and data collection techniques used in this study are observation and tests. From the observation results, it is known that the overall teacher activity in cycle I with the application of Make a Match media is 68.75%, this figure is in the range of 50% - 74% in the sufficient category. The results of observations of overall student activity in cycle I, namely 67.5% were in the range 50% - 74% in the sufficient category with the percentage of completeness of student learning outcomes in cycle I was 64.81% in the sufficient category. Overall teacher activity in cycle II was 93.75%, this figure was in the range of 75% - 87% in the good category. The results of observations of overall student activity in cycle II, namely 82.55% were in the range 75% - 87% in the good category with the percentage of completeness of student learning outcomes in cycle II was 70.85% in the good category. Overall teacher activity in cycle II was 93.78% in the range of 88-100% with very good category. Overall student activity in cycle II, which is 92.5%, is in the range of 88-100% in the very good category, with the percentage of completeness of student learning outcomes in cycle II, namely 80.75% in the good category. Thus it can be concluded that the application of Make a Match learning media can improve student learning outcomes in Theme 8 "Praja Muda Karana" class III SD PAB 23 Patumbak